Effectiveness of silica based sol-gel microencapsulation method for odorants and flavors leading to sustainable environment - Ashraf, Muhammad Aqeel; Khan, Ayesha Masood; Sarfraz, Maliha; Ahmad, Mushtaq (Frontiers in Chemistry, 2015)
Microencapsulation has become a hot topic in chemical research. Technology mainly used for control release and protection purposes. The sol–gel micro encapsulation approach for fragrance and aroma in porous silica-based materials leads to sustainable odorant and flavored materials with novel and unique beneficial properties. Sol-gel encapsulation of silica based micro particles considered economically cheap as capital investment in manufacturing is very low and environmentally friendly. Amorphous sol–gel SiO2 is non-toxic and safe, whereas the sol–gel entrapment of delicate chemicals in its inner pores results in pronounced chemical and physical stabilization of the entrapped actives, thereby broadening the practical utilization of chemically unstable essential oils. Reviewing progress in the fabrication of diverse odorant and flavoured sol-gels, shows us how different synthetic strategies are appropriate for practical application with important health and environmental benefits.